Perancangan Sistem Informasi Akademik Untuk Mengetahui Perkembangan Nilai Siswa Berbasis Mobile Pada Sekolah RA. Ar-Rahmah - Khopipah Febriyanti; Dola Irwanto (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The academic information system is an important application for schools in managing student data. However, there are still many schools that do not have an academic information system that is comprehensive and easily accessible to users, especially parents. Therefore, this study aims to design a mobile web-based academic information system that can assist parents in monitoring the progress of student scores in schools Ra. Ar-Rahmah. The method used in this research is prototyping, which is a system development method that uses an approach to make a program quickly and gradually so that it can be evaluated by the user. The results of this study are a mobile web-based academic information system that can be used by teachers to enter student scores and parents of students to see progress in student grades in real-time. This system is expected to facilitate the management of student grades and increase efficiency in schools. ar-rahmah.